Nature-Identical Compounds and Organic Acids Reduce E. coli K88 Growth and Virulence Gene Expression In Vitro - Bonetti, Andrea (Toxins (Basel), 2020)
Post-weaning diarrhoea (PWD) is one of the long-standing challenges in pig husbandry. Due to the risks of resistance caused by antibiotics (AB) misuse, conventional treatments against Escherichia coli K88 (E. coli K88), the PWD etiological agent, urgently need to be replaced. Organic acids (OA) and nature-identical compounds (NIC) are currently finding a central role in infection management thanks to their recognized antimicrobial activity. This study investigated the susceptibility of an E. coli K88 field strain to a wide panel of AB, NIC, and OA. Secondly, we evaluated the ability of sub-lethal doses of the most active compounds to modulate the expression of E. coli K88 virulence genes. Results showed that the bacterial strain was resistant to many of the tested antibiotics, but an antimicrobial action was registered for selected NIC and OA. The quantitative PCR analysis revealed that thymol, carvacrol, eugenol, and benzoic acid were able to downregulate (p < 0.05) the expression of bacterial genes related to motility, adhesion to enterocytes, heat-labile (LT) and heat-stable (ST) toxin secretion, quorum sensing, and biofilm formation. Therefore, this study demonstrated that selected OA and NIC not only control E. coli K88 growth but also modulate the expression of many virulence genes at sub-lethal doses, thus offering new insights on their mechanism of action and suggesting a powerful tool to manage PWD.